Analisis Peran Moderasi Pertumbuhan Dana Pihak Ketiga Pada Hubungan Antara Risiko Kredit, Financial Performance Dan Kecukupan Modal - Moh. Samsul Arifin; Hendy Tannady; Sutrisno Sutrisno; Ahmad Junaidi; Joko Ariawan (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this study to analyze the effect of capital adequacy and credit risk on bank financial performance inmoderated by growth of third party funds. The population used in this study are commercial bank listed on the IndonesiaStcok Exchange (IDX) from 2016 to 2020 based purposive sampling method and the samples consisting are 18companies. This research analysis used moderated regression analysis (MRA). The results are capital adequacy hasnot effect on financial performance, credit risk has significant negative on financial performance, growth of third partyfunds not able to moderate the effect of capital adequacy and credit risk on bank financial performance. Keywords: Capital Adequacy, Credit Risk, Financial Performance, Growth Of Third Party Funds